Guided inquiry laboratory to improve research skills of prospective biology teachers - Zuhdan Kun Prasetyo; Djukri Djukri; Djohar Maknun (Institute of Advanced Engineering and Science, 2022)
This study described guided-inquiry laboratory impact on increase in research skills of prospective biology teachers. Skill research indicators are designing, implementing, and reporting. This study was a non-equivalent control group design using experimental and control groups. Data were collected from 60 participants through observation of research skill indicators, namely designing, performing, and reporting then analyzed quantitatively-descriptively. The sample was selected using purposive sampling. The results confirmed that the guided-inquiry laboratory application has a more effective impact on improving research skills than ordinary learning. Each indicator of research skills (designing, performing, and reporting in the experimental class) meets the